2019
DOI: 10.1080/10717544.2019.1602796
|View full text |Cite
|
Sign up to set email alerts
|

Cubic and hexagonal liquid crystals as drug carriers for the transdermal delivery of triptolide

Abstract: The purpose of this study was to develop and evaluate triptolide-loaded cubic and hexagonal liquid crystals for transdermal drug delivery systems (TDDSs). We prepared and characterized triptolide-loaded lyotropic liquid crystals and evaluated for their percutaneous permeation properties in vitro and in vivo . We then used the adjuvant arthritic rat model and HaCaT cells to analyze the pharmacodynamics and conduct cell-stimulating studies of these liquid crystals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The black view under the cross-polarized optical microscope indicates the isotropic phase of the cubosomes as previously reported. 20 , 38 Consequently, the presence of OA alters the GMO effective packing parameter that induces the phase transition from the cubic phase (cubosomes) to the 2D hexagonal phase (hexosomes) 17 , 39 as shown in Figure S2B , which indicates the anisotropic phase with a fanlike structure of hexosomes as previously reported. 38 , 40 The obtained hexosomes appeared as a homogenous milky-like dispersion.…”
Section: Resultssupporting
confidence: 65%
“…The black view under the cross-polarized optical microscope indicates the isotropic phase of the cubosomes as previously reported. 20 , 38 Consequently, the presence of OA alters the GMO effective packing parameter that induces the phase transition from the cubic phase (cubosomes) to the 2D hexagonal phase (hexosomes) 17 , 39 as shown in Figure S2B , which indicates the anisotropic phase with a fanlike structure of hexosomes as previously reported. 38 , 40 The obtained hexosomes appeared as a homogenous milky-like dispersion.…”
Section: Resultssupporting
confidence: 65%
“…Patch refers to a flake preparation made of drugs and suitable materials that can be pasted on the skin for topical administration. Transdermal patches are usually composed of four layers, the impermeable backing layer, drug containing matrix layer, adhesive layer, and peelable anti adhesion protective layer (Pastore et al., 2015 ). The patch can slowly release the drug, allowing it to penetrate the skin and maintain a constant plasma concentration (Nalamachu & Gudin, 2020 ).…”
Section: Ra Transdermal Dosage Formmentioning
confidence: 99%
“…Their structures and chemical properties of V 2 and H 2 phases are similar to those of cell membranes, allowing drugs to penetrate stratum corneum for transdermal delivery [ 145 ]. Shan et al [ 146 ] reported that the IC 50 of triptolide-loaded V 2 group and H 2 group in HaCaT cells were respectively 158 and 23 times that of free triptolide group, indicating their excellent anti-arthritic effects with low skin irritation.…”
Section: Strategies To Reduce Toxicity Of Triptolidementioning
confidence: 99%